Integrated proteome and malonylome analyses reveal the neutrophil extracellular trap formation pathway in rheumatoid arthritis - Hu, Biying; Li, Dandan; Zeng, Zhipeng; Zhang, Zeyu; Cao, Rui; Dong, XiangNan; Yun, Chen; Li, Ling; Krämer, Bernhard; Morgera, Stanislao; Hocher, Berthold; Tang, Donge; et al. (Journal of proteomics, 2022)
Rheumatoid arthritis (RA) is an autoimmune inflammatory disease of unknown etiology in which the posttranslational modifications (PTMs) of proteins play an important role. PTMs, such as those involved in the formation of neutrophil extracellular traps (NETs), have been well studied. The excessive formation and release of NETs can mediate inflammation and joint destruction in RA. It has been gradually recognized that lysine malonylation (Kmal) can regulate some biological processes in some prokaryotes and eukaryotes. However, less is known about the role of Kmal in RA. We therefore performed proteome and malonylome analyses to explore the proteomic characteristics of the peripheral blood mononuclear cells from 36 RA patients and 82 healthy subjects. In total, 938 differentially expressed proteins (DEPs) and 42 differentially malonylated proteins (DMPs) with 55 Kmal sites were detected through a liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based analysis. Functional analysis showed that two DEPs with four malonylated sites and one DMP with a malonylated site were identified in the neutrophil extracellular trap formation (NETosis) pathway. Altogether, this study not only describes the characteristics of the malonylome in RA for the first time, but it also reveals that malonylation may be involved in the NETosis pathway. - Significance - This is the first report that reveals the proteomic features of Kmal in RA through a LC-MS/MS-based method. In this study, we found that several key DMPs were associated with the NETosis pathway, which contributes to the development of RA. The present results provide an informative dataset for the future exploration of Kmal in RA.